Internet for language arts - Mares, Linda; Wilson, Nancy Rabuck; Educational Video Network, Inc. (Huntsville, Tex. : Educational Video Network, 2001)
Covers searching for accurate information on the Internet within the context of language arts.
Videography, Linda Mares, Seth Conway, Ronald Greene, Shannon McWhirter ; Graphics, Elizabeth Sharp ; Script editors, Alisse Wobser, Anne Russell.
Narrator: Thomas F. Soare.
Keywords: Computer network resources; Internet in education; Language arts